Pengembangan Sistem Hidroponik Otomatis-Modern Berbasis Panel Surya dan Baterai - Luthfansyah Mohammad; Suyanto; Muhammad Khamim Asy’ari; Asma’ul Husna; Sarinah Pakpahan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The flexibility and the easiness of farming using modern hydroponic method have increased the installation requirements. The various types of plants can be applied to modern hydroponic systems, so this method has potential to be applied in various regions. However, not all regions have access to electricity networks. In fact, to operate modern hydroponic systems, an adequate supply of electrical power is required. In addition, a proper design becomes crucial part which has function to maintain the quality of inorganic substances as needed, accurately and automatically measured. Moreover, the system could be set in off-grid mode. Therefore, a further research of automatic hydroponics was conducted to solve various problems. The experimental data shows that the system is working accurately. The percentage of error sensor is not more than 10.75% and the accuracy of actuator performance is 100%. The system is also capable of working for a full day through a solar panel system of 100 WP and a battery of 27 Ah. In conclusion, the design of the automatic hydroponic system is capable of self-maintaining nutritional and pH value, solving artificial irradiation time problem, while simultaneously operating in various areas in a portable manner.